Teaching Competencies of Provisional Senior High School Teachers in Zone 2, Division of Zambales - Boquirin, Nikka D. (Future Science / FSH-PH Publications, 2025)
The importance of effective teaching in education is undeniable, as it directly impacts student learning outcomes. This study focused on assessing the teaching competencies of provisional Senior High School teachers and their relationship to teaching performance. This study utilized a descriptive- correlational research design and a quantitative method to examine 109 provisional teachers from 16 public secondary schools in Zone 2, Schools Division of Zambales, using a total population sampling technique. A three-part survey questionnaire was used to collect data on demographic profiles, performance ratings, and teaching competence levels during the fourth quarter of the 2023–2024 school year. Inferential analysis used Analysis of Variance (ANOVA) to test for significant differences between competencies and teacher profiles, and Pearson-r correlation to identify relationships between competencies and performance levels. The study found that 94.5% of teachers had an outstanding performance rating. While they showed competence in communication and classroom management, there was a need for development in subject matter mastery, instructional, and assessment skills. The data revealed that 54.13% of teachers had 0-5 years of experience, and 67.89% lacked national certificates. A significant finding was that attending relevant seminars and workshops significantly impacts subject matter mastery. There was a slight, but not statistically significant, relationship (r = 0.121) between teaching competency and performance evaluations. The study recommends implementing a proposed action plan to address competency gaps and suggests future research compare different professional development models to find the most effective approach.